Pengaruh Model Pembelajaran CTL Berbantuan Media Audiovisual dengan Pendekatan Deep Learning Terhadap Kemampuan Berpikir Kritis - Yuda Nugraha; Rendra Gumilar; Ai Nur Solihat (Smart Education, 2026)
This study aims to examine the effect of the CTL assisted by audiovisual with a deep learning approach on the critical thinking skills of tenth-grade students at SMA Negeri 2 Tasikmalaya. Although the effectiveness of CTL has been widely investigated, studies integrating CTL, audiovisual media, and a deep learning approach simultaneously in economics learning remain limited, creating a research gap that underpins this study. The novelty of this research lies in examining the synergistic effect of these three components as a unified instructional intervention. The study employed a quasi-experimental method using a non-equivalent control group design. The research instrument was an essay test measuring critical thinking skills based on Ennis's indicators. The results revealed a significant improvement in the experimental group, with the mean score increasing from 36.22 on the pretest to 85.84 on the posttest, while the control group improved from 35.55 to 73.13. The independent samples t-test showed a significance value of 0.000 (p < 0.05), with a Cohen's effect size of 1.29, indicating a very large effect. It can be concluded that the CTL model assisted by audiovisual media with a deep learning approach is effective in improving students' critical thinking skills in economics learning.